The virgin lands campaign and the occurrence of foot-and-mouth disease and anthrax in the Republic of Kazakhstan (1955–1970) - Mukhanbetkaliyev, Yersyn Y.; Kadyrov, Ablaikhan S.; Berdikulov, Maxat A.; Mukhanbetkaliyeva, Aizada A.; Kadyrov, Alimzhan S.; Zhanabayev, Assylbek A.; Korennoy, Fedor I.; Perez, Andres M.; Abdrakhmanov, Sarsenbay K. (Frontiers in Veterinary Science, 2025)
The campaign for the development of virgin lands in Kazakhstan (1955–1970) was one of the most ambitious programs implemented by the Soviet government, which, arguably, resulted in both positive and negative consequences for the country. The campaign brought, at the same time, development, environmental degradation, and a dramatic cultural change to Kazakhstan. A barely explored aspect of the virgin lands campaign is related to its impact on the epidemiology of animal diseases. This paper describes, for the first time, the changes experienced by Kazakhstan during the implementation of the virgin lands campaign, offering a perspective on how those changes may have affected the occurrence of foot-and-mouth disease (FMD) and anthrax. Newly organized livestock premises and processing plants were created, which increased the concentration and intensification of animal production, in the absence of effective disease control plans. The initial increase in FMD prevalence may have been explained by the concentration of susceptible animals in the absence of appropriate control measures, followed by a decrease in disease incidence, probably explained by the enhancement of control measures associated with the formalization of livestock production, including improvements in vaccine quality. In contrast, soil degradation and the increase in the number of livestock, which resulted in a large number of animals buried in inappropriate conditions, may explain the sustained increase in the incidence of anthrax. The results presented here help to document the history of animal diseases in the country and ultimately contribute to the design of holistic strategies to support Kazakhstan’s development.